THE CORRELATIONS BETWEEN BEHAVIOR OF WEARING MASK AND FACIAL HYGIENE WITH ACNE VULGARIS IN CLINICAL STUDENTS OF SWADAYA GUNUNG JATI UNIVERSITY - Wahid, Adhitya Abdurrahman; Rahayu, Frista Martha; Risman, Muhammad (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2024)
Acne vulgaris is a multifactorial skin disease characterized by inflammation of the pilosebaceous glands. The use of masks is one of the risk factors in the emergence of acne vulgaris, while facial hygiene is something that needs to be considered by someone in the behavior of using masks. The aims of this study is to analyze the relations between the behavior of wearing masks and facial hygiene with the incidence of acne vulgaris. This study is an analytic observational study with a cross-sectional design. The sample used in this study was 70 people. The sampling technique used is purposive sampling. Data were analyzed using the Spearman correlation test and logistic regression test. Spearman correlation test analysis obtained p-values of 0.030 and 0.013 (p-value <0.05) which means there is a relationship between the behavior of wearing masks and facial hygiene with the incidence of acne vulgaris. Meanwhile, the multivariate analysis shows that the Odd ratio values for the behavioral variables of using masks and facial cleanliness are 1,947 and 1,827 for risk of ace vulgaris. There is a significant relationship between the behavior of using masks and facial hygiene with the incidence of acne vulgaris. The behavior of wearing mask has a 1,9 times higher risk, while facial hygiene has a 1,8 times higher risk of developing acne vulgaris in students of the Medical Profession Study Program, Faculty of Medicine, Swadaya Gunung Jati University at Waled Hospital, Cirebon district.